Effect of Neem (Azadirachta indica L.) on Lipid Oxidation in Raw Chilled Beef Patties - Manel Ouerfelli; Juliana Villasante; Leila Bettaieb Ben Kaâb; MaríaPilar Almajano (MDPI AG, 2019)
The aim of this study was to determine the total polyphenol content, radical scavenging and antimicrobial activities of Azadirachta indica (A. indica) and to evaluate their effect on shelf-life stability of raw beef patties during refrigerated storage at 4 ± 1 °C. During 11 days of storage, the antioxidant effect of A. indica on ground beef meat was investigated by the determination of lipid oxidation, pH, anti-radical activity, color, hexanal content, and microbial growth. The results obtained showed that fresh A. indica leaves and synthetic conservative behaved in the same way and retarded the lipid oxidation of chilled beef patties while increasing their pH (5.40 and 5.45, respectively). It can also be said that A. indica limited the loss of color, reduced the metmyoglobin formation (36.70%) and had a significant effect on bacterial growth and hexanal content. In addition, the results obtained through anti-radical and antimicrobial properties showed proportional values of total polyphenol content and radical scavenging activity of leaf extracts as they showed their antimicrobial effect against some bacteria such as Staphylococcus aureus and Micrococcus luteus, among others. These results support the involvement of A. indica in the food industry as a natural antioxidant that could replace synthetic ones.